E-money Usage: Benefits and Ease of Use in Indonesia - Hadiwidjaja, Audrey Erin; Dewi, Liliana (Jurnal Economia, 2025)
AbstractThe digitalization era emerges a cashless lifestyle. The study aims to determine the effect of perceived usefulness and ease of use on the intention of using e-money, with subjective norms and social image as moderators. This study uses a quantitative method by distributing online questionnaires to 197 respondents in Surabaya who have used e-money for at least three months. The results of the questionnaire data were processed with SmartPLS 3.0. The urgency of the study is that the use of social image and subjective norms as external variables still needs to be studied. All of the objectives of this study are significant, except that social image can weaken the influence of intention in using electronic money, so this is the study's uniqueness.